P-148 Designing and developing on-line education resources about sexuality with co-researchers. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Blackburn, Maddie; Earle, Sarah; Watts, Lucy
Abstract : Background: Inclusive research indicates that the decision-making process is one in which the 'professional' researcher and the 'co-researcher'(s) have equal weight and authority within the research process and collaborate throughout. Aims: In this presentation, we shall draw on our current project, focussing on the merits and some of the challenges in engaging co-researchers in inclusive research. This project addresses the design and development of on-line education resources (OERs) about sex, intimacy and relationships for and with young people, age 16+, with life-limiting and or life threatening conditions (LLTCs). This builds upon previous research but where young adults with LLTCs were consulted but not formally contracted as co-researchers. Methods: This project uses an inclusive, action research model designed to support the transition of young people who are life-limited or life-shortened, by developing their confidence in talking about sex, intimacy and relationships with family, friends, care practitioners and other carers. Findings/Results: The presentation will address the merits and some of the ethical challenges of collaborating with co-researchers who have LLTCs; particularly when the university researchers also include both academics and policy researchers with a clinical background. We shall discuss how, together, we have developed, on-line education resources about relationships, intimacy and sex via The Open University's, Open Learn Portal. Addressing the duty of care to individuals with a LLTC who may become ill during the project should also be balanced with the responsibilities of researchers to complete and deliver a funded project in a timely fashion. These aspects will also be addressed. Conclusion: Much innovative, inclusive research is methodologically orientated, and may focus more about the process rather than the deliverables and the outcomes (Blackburn, 2018). This project focuses on the outcomes, contribution to knowledge and the impact about a very specific, niche area of sexuality, whilst seeking to include the important methodological innovations of co-research.